A new genus and species of net-winged midge from Madagascar (Diptera: Blephariceridae: Blepharicerinae) - Courtney, Gregory W. (Zootaxa, 2015)
Larvae of a species from the subfamily Blepharicerinae were first discovered in the 1950’s, but the lack of additional records prevented description of the species. A recent study of important additional specimens from the late Brian Stuckenberg has provided the basis for describing this unusual fly. This paper provides a description of larvae, pupae, and adults of Aphromyia stuckenbergi gen. et sp. nov., and a brief discussion of its phylogenetic position within the family. The latter is confounded by marked adult colocephaly (reduction of the head) and concomitant reduction in mouthparts, and by lack of recent collections that would permit molecular analyses and further morphological study. Known from only two collections, the most recent nearly 60 years ago, this highly endemic and rare fly is arguably one the most endangered species in Madagascar.